Interaction with soil enhances the toxic effect of iodide and iodate on barley (Hordeum vulgare L.) compared to artificial culture media during initial growth stage - Duborská, Eva; Urík, Martin; Kubová, Jana (Archiv für Acker- und Pflanzenbau und Bodenkunde, 2018)
Iodine is an essential trace element for humans, and while plants play an important role in its supplementation, they can also be subject to iodine toxicity. Herein, comparison of iodide and iodate effects on barley (Hordeum vulgare L.) development was evaluated in laboratory experiments when it was cultivated in iodine-spiked agar cultivation media and agricultural soil. Our results show that iodine toxicity is highly dependent on its chemical form and also reflects growth substrate type. Barley responses to iodine presence in agar and soil media suggest that iodide has more severe inhibitory effects than iodate on plant growth. Furthermore, the detrimental effect of iodine notably increased in soil with biomass synthesis as the most sensitive physiological parameter to adverse iodide and iodate effects. However, mild iodate and iodide stimulation of barley growth was observed which implies they are beneficial for growth at low concentrations. These effects were more intense when iodine was applied as iodide, especially in soil cultivation system where natural geochemical processes lead to alteration in iodine speciation which significantly increases plant sensitivity to iodine toxicity.